ANALYSIS OF COORDINATION BETWEEN SIGNALLED INTERSECTIONS (CASE STUDY: RANCABANGO INTERSECTION AND BANTAR INTERSECTION, TASIKMALAYA CITY) - Mentari Pagi Febriana; Andhy Romdani; Empung (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
The large number of intersections in Tasikmalaya City, particularly the nearby Rancabango and Bantar intersections, causes vehicles to frequently stop at each intersection due to red lights. To reduce delays and queues, an analysis of coordination between signalized intersections was conducted. Data was collected through field surveys conducted from April 21, 2025, to May 6, 2025, covering geometric data, signal timing, traffic volume, and vehicle speed. The analysis was conducted using the 2023 Indonesian Road Capacity Guidelines. The results showed that the two intersections were not yet coordinated. From the three plans, a new cycle time of 71 seconds was obtained with an offset of 60 seconds between the Rancabango Intersection and the Bantar Intersection and a bandwidth of 18 seconds for the direction of movement from the Rancabango Intersection to the Bantar Intersection and 31 seconds for the opposite direction. With the implementation of coordination between signalized intersections, intersection performance showed improvement, marked by a decrease in vehicle queue length from 69.22 meters to 62.39 meters and a decrease in average delay from 36.75 seconds/SMP to 35.63 seconds/SMP.